Waterway to Go! Excavations at Lochrin Basin, Edinburgh. Issue 1 (March 2022) - Paton, Kevin
Abstract : Regeneration of the former industrial areas surrounding Tollcross, Edinburgh, has provided opportunities to rediscover some of the important elements of the area's industrial past. Constructed as a private enterprise that linked into the newly constructed canal network, Lochrin Basin was a significant example of an ambitious family enterprise of the 19 th century. Due to its private status and abandonment in the late 19 th century, it was infilled and was unfortunately not given the same protected status as the rest of the canal network. However, excavations at the site of the former canal basin revealed that it survived mainly intact, with some surprising elements encountered. As part of the post-excavation process, a programme of documentary research was undertaken to provide a more comprehensive history of Lochrin Basin's inception, construction, and use.